2017
DOI: 10.1590/abd1806-4841.20175870
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metastases in a patient with no previous diagnosis of cancer: diagnostic challenge

Abstract: On rare occasions, skin lesions are the first local of metastatic manifestation of internal malignancies. In case of no previous diagnosis of these tumors, the approach of suspicious skin lesions becomes a challenge, especially in differentiating cutaneous metastases and adnexal primary neoplasms. Currently, besides epidemiologic, dermoscopic and histopathologic aspects, the evaluation also integrates immunohistochemical exams and cell markers such as p40 and p63, highly specific for skin metastases. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In 2013, a Brazilian study demonstrated that the most common sites of cutaneous metastases are the chest (31.94% of cases) followed by the abdomen (20.37%) and scalp (14.81%). In women, the most common primary malignancy was breast cancer (63.19%), intestines (10.41%) and lung (4.16%), which tends to metastasize later to the anterior thoracic wall [ 2 , 6 ]. Although cutaneous metastasis most frequently originates from breast cancer, it rarely occurs as the first manifestation of this malignancy [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2013, a Brazilian study demonstrated that the most common sites of cutaneous metastases are the chest (31.94% of cases) followed by the abdomen (20.37%) and scalp (14.81%). In women, the most common primary malignancy was breast cancer (63.19%), intestines (10.41%) and lung (4.16%), which tends to metastasize later to the anterior thoracic wall [ 2 , 6 ]. Although cutaneous metastasis most frequently originates from breast cancer, it rarely occurs as the first manifestation of this malignancy [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our case showed a sudden development of multiple erythematous patches that rapidly ulcerated. Cutaneous metastases from breast cancer are most commonly reported as multiple, firm, hyperpigmented, painless nodules, followed by papules, erysipelas-like, alopecic, and sclerotic plaques which may retract the skin [ 2 , 6 ]. In a review of 164 patients, the most frequent manifestations were papules and/or nodules (80%), followed by telangiectatic carcinoma (11.2%), erysipeloid carcinoma (3%), carcinoma en cuirasse (3%), alopecia neoplastica (2%) and zosteriform pattern (0.8%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations